2018
DOI: 10.2298/ijgi1802195g
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity overview of soda pans in the Vojvodina region (Serbia)

Abstract: Due to their specific physical and chemical properties of water and soil soda pans of the Vojvodina region represent a unique type of habitats. Salinity is a major structuring factor which strongly affects species richness. Many halotolerant, alkalotolerant and halophilic organisms, together with numerous eurytopic elements inhabit these kinds of ecosystems. In this review we tried to compile the biodiversity information from various literature sources and give the best representation of what can be expected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The status of soda pans is dependent upon the maintenance of their natural hydrological cycle (Stenger‐Kovács et al, ). Drying out is a natural and required feature of the pans (Gavrilović et al, ), and this, in turn, can radically reduce functional diversity (B.‐Béres et al, ). Under pristine ecological status, not only small species numbers and species‐based diversity (Stenger‐Kovács et al, ), but also restricted trait variations can be found in the present study: Motile, small, elongated diatom species are characteristic (e.g., Nitzschia austriaca Hustedt, Nitzschia aurariae Cholnoky , Craticula elkab (O. Muller ex O. Muller) Lange‐Bertalot, Kusber & Cocquyt), indicating the harsh (high conductivity and turbidity, temporary drying out) environment (Stenger‐Kovács et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The status of soda pans is dependent upon the maintenance of their natural hydrological cycle (Stenger‐Kovács et al, ). Drying out is a natural and required feature of the pans (Gavrilović et al, ), and this, in turn, can radically reduce functional diversity (B.‐Béres et al, ). Under pristine ecological status, not only small species numbers and species‐based diversity (Stenger‐Kovács et al, ), but also restricted trait variations can be found in the present study: Motile, small, elongated diatom species are characteristic (e.g., Nitzschia austriaca Hustedt, Nitzschia aurariae Cholnoky , Craticula elkab (O. Muller ex O. Muller) Lange‐Bertalot, Kusber & Cocquyt), indicating the harsh (high conductivity and turbidity, temporary drying out) environment (Stenger‐Kovács et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of diatoms in saline habitats have been sporadic, not only in Serbia, but also in Europe. Gavrilović et al (2018) provide an overview of diatom research in this type of habitat in Serbia. However, a detailed study has been done only on Lake Velika Rusanda, an alkaline soda lake, where 27 diatom taxa were recorded (Vidaković et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Organisms capable of surviving in these environments developed some adaptations which help them to overcome challenges caused by extreme factors like osmotic stress or desicca-tion in temporary ponds. Thus, mainly alkaliphilous and salt-tolerant species can be found in salt ponds and marshes (Stenger-Kovács & Lengyel 2015;Żelazna-Wieczorek et al 2015;Ács et al 2017;Gavrilović et al 2018). Moreover, it is known that the specific nature of these habitats can lead to regional endemicity in some taxonomic groups (Williams 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continental saline waters are unique and extreme environments, inhabited by specific biota, with high conservation value (Williams 2002;Gavrilović et al 2018). In recent years, one type of these habitats has been attracting the attention of biologists who have tried to develop a system of new biological quality elements or indicators for assessment of its ecological status.…”
Section: Introductionmentioning
confidence: 99%